Implementasi Pola Asuh Orang Tua Terhadap Perkembangan Mental Anak Berkebutuhan Khusus (Abk) (International Forum of Researchers and Lecturers, 2023)
Parents are the primary and first educators for their children, because it is from them that children first receive education. The role of parents as the main and first educators for children is also due to their heredity being destined to be parents who give birth. So naturally, like it or not, parents who are the main and first responsible for children can receive education. The parenting style of parents of children with special needs is very influential in the survival of children with special needs in the future, if parents cannot choose the right parenting style it will have an impact on the child's development process. Children with special needs are children who need extra attention from the people around them, both parents, teachers, relatives and peers. Children who have special needs do not have to be shunned or avoided but rather need to be approached and given assistance, so that the child's potential can develop properly. For children who experience health problems, both physically and mentally, special services should be given compared to other children. Likewise in learning activities, they must be provided with facilities and infrastructure according to their needs which can support the success of learning, especially to help their physical and mental development towards a better one.